Memory for Multiple Cache Locations and Prey Quantities in a Food-Hoarding Songbird - Armstrong, Nicola; Garland, Alexis; Burns, Kevin C. (Frontiers in Psychology, 2012)
Most animals can discriminate between pairs of numbers that are each less than four without training. However, North Island robins (Petroica longipes), a food hoarding songbird endemic to New Zealand, can discriminate between quantities of items as high as eight without training. Here we investigate whether robins are capable of other complex quantity discrimination tasks. We test whether their ability to discriminate between small quantities declines with 1. the number of cache sites containing prey rewards and 2. the length of time separating cache creation and retrieval (retention interval). Results showed that subjects generally performed above chance expectations. They were equally able to discriminate between different combinations of prey quantities that were hidden from view in 2, 3 and 4 cache sites from between 1, 10 and 60 seconds. Overall results indicate that North Island robins can process complex quantity information involving more than two discrete quantities of items for up to one minute long retention intervals without training.